Infertility: effects of weight loss on the hormonal profile in obese, infertile women - Hollmann, Michaela; Runnebaum, Benno; Gerhard, Ingrid (Human reproduction, 1996)
This study was designed to investigate the effects of weight loss in obese, infertile women with special interest in changes of blood hormones, menstrual function and pregnancy rate. Blood glucose, insulin, C-peptide and different steroid and pituitary hormones during oral glucose loading were determined in a group of 58 obese women with menstrual irregularities. Of the 58 women, 35 took part in a weight-reducing programme lasting 32 ± 14 weeks (mean ± SD) with a weight loss of 10.2 ± 7.9 kg (therapy group). At the time of first oral glucose tolerance testing, insulin resistance was a feature in 85% of the women in the therapy group, and 22% were hyperandrogenaemic Weight loss resulted in a significant reduction in blood glucose, insulin, androstenedione, dihydrotestosterone and oestradiol concentrations. The pregnancy rate was 29% in this group and of them, 80% showed an improvement of their menstrual function. Thus, weight reduction is the appropriate treatment for women with obesity-related endocrine derangement, menstrual irregularity and infertility.